Diferenças estratégicas entre mecanismos fisiológicos C3 e C4 frente a estresses abióticos e aplicação de acetilcolina - Oliveira, Bruno Felipe Picoli (2024)
Soybean and corn are among the main crops currently produced due to their high protein and oil value, with high value in the agricultural commodities market. However, the increased occurrence of droughts combined with high temperatures can cause severe damage to several physiological processes of these crops, affecting their productive potential. One way to mitigate the effects of abiotic stress is to apply small concentrations of bioregulators, including acetylcholine (ACh). ACh acts on different physiological processes of the plant and plays an important role in defense responses to abiotic stresses. In view of the above, the objective of this study was to compare the potential effects of exogenous application of ACh on soybean and corn crops grown under conditions of associated water deficit and high temperature. The plants were grown in a greenhouse and when they reached the V3 stage, some of them were taken to a growth chamber, where they were exposed for five days to 38/28°C (day/night) and irrigation with 30% of field capacity. After the stress imposition stage and physiological (water potential and gas exchange) and biochemical evaluations were completed, the plants were rehydrated and returned to temperature control conditions. After 24 hours (6th day), specific measurements of gas exchange (ETR, A, E, gs, Ci, EiC and EUA) and biochemical analyses (activity of the enzymes SOD, POD, APX and concentrations of O2-, H2O2 and MDA) were performed again, as well as growth parameters. The experiments were conducted in a completely randomized experimental design, with a 2 x 2 factorial arrangement (absence and presence of stress and absence and presence of ACh at a concentration of 2 mM), totaling 4 treatments and 9 replicates. ACh was efficient in activating antioxidant enzymes in both crops, but soybean showed an increase in the parameters of A, gs, E, ETR and EC in response to ACh application, while in corn it was not possible to observe the same positive response during the stress period. Subsequently, on the 6th day, all photosynthetic parameters showed recovered values in the soybean crop, while in the corn crop the bioregulator did not result in this response. In the morphological evaluation, the corn plants showed an increase in shoot biomass and number of leaves in response to the application of ACh, while in the soybean plants there was a reallocation of photoassimilates for the production of biomass in the root. It is concluded that in this study, soybean responded better when considering together the biochemical, photosynthetic and morphological parameters against abiotic stress and application of ACh, compared to corn.